Users' Assessment of the Value of Advertisements on Social Networking Sites: A conceptual Study - Deraz, Hossam (International Review of Management and Marketing, 2018)
The aim of this paper is to propose a conceptual framework addressing factors that predict users' assessment of the value of ads on social networking sites. The basic unit of analysis is the SNSs' user. The action scene is composed of a set of components that together shape the outcomes of the model to identify these factors. The suggested framework consists of five belief factors (information value, entertainment value, credibility value, irritation value, and interactivity value), one motive factor (individuals' pre-purchase search motivation), in addition to two social factors (Social influence, and national culture). The study aimed to characterize these key elements of the framework, their relationship, and interactions with the perceived value of advertisements. This paper intends to create a common understanding of the basic concepts and a shared conceptual model among scholars researching advertisements on online social networks. Keywords: Online Social Networks, Facebook, Belief factors, Pre-purchasing intention, Social influence, Source credibility, electronic marketing JEL Classifications: M31, M37 DOI: https://doi.org/10.32479/irmm.7117